WACK!: art and the feminist revolution - Butler, Cornelia H.; Mark, Lisa Gabrielle; Museum of Contemporary Art (Los Angeles, Calif); Butler, Cornelia H.; Mark, Lisa Gabrielle; Museum of Contemporary Art (Los Angeles, Calif) (Museum of Contemporary Art, 2007)
Groundbreaking art from a revolutionary era, featuring work by more than 120 international artists, from Louise Bourgeois and Yoko Ono to Martha Rosler, Marina Abramović, and Cindy Sherman. There had never been art like the art produced by women artists in the 1970s, and there has never been a book with the ambition and scope of this one about that groundbreaking era. WACK! documents and illustrates the impact of the feminist revolution on art made between 1965 and 1980, featuring pioneering and influential works by artists who came of age during that period, Chantal Akerman, Lynda Benglis, Theresa Hak Kyung Cha, Valie Export, Mary Heilmann, Sanja Iveković, Ana Mendieta, Annette Messager, and others, as well as important works made in those years by artists whose careers were already well established, including Louise Bourgeois, Judy Chicago, Sheila Levrant de Bretteville, Lucy Lippard, Alice Neel, and Yoko Ono. The art surveyed in WACK! includes work by more than 120 artists, in all media, from painting and sculpture to photography, film, installation, and video, arranged not by chronology but by theme: Abstraction, "Autophotography," Body as Medium, Family Stories, Gender Performance, Knowledge as Power, Making Art History, and others. WACK!, which accompanies the first international museum exhibition to showcase feminist art from this revolutionary era, contains more than 400 color images. Highlights include the figurative paintings of Joan Semmel; the performance and film collaborations of Sally Potter and Rose English; the untitled film stills of Cindy Sherman; and the large-scale, craft-based sculptures of Magdalena Abakanowicz. Written entries on each artist offer key biographical and descriptive information and accompanying essays by leading critics, art historians, and scholars offer new perspectives on feminist art practice. The topics, including the relationship between American and European feminism, feminism and New York abstraction, and mapping a global feminism, provide a broad social context for the artworks themselves. WACK! is both a definitive visual record and a long-awaited history of one of the most important artistic movements of the twentieth century. Essays by: Cornelia Butler, Judith Russi Kirshner, Catherine Lord, Marsha Meskimmon, Richard Meyer, Helen Molesworth, Peggy Phelan, Nelly Richard, Valerie Smith, Abigail Solomon-Godeau, Jenni Sorkin Artists include: Marina Abramović, Chantal Akerman, Lynda Benglis, Dara Birnbaum, Louise Bourgeois, Judy Chicago, Lygia Clark, Jay DeFeo, Mary Beth Edelson, Valie Export, Barbara Hammer, Susan Hiller, Joan Jonas, Mary Kelly, Maria Lassnig, Linda Montano, Alice Neel, Senga Nengudi, Lorraine O'Grady, Pauline Oliveros, Yoko Ono, Orlan, Howardena Pindell, Yvonne Rainer, Faith Ringgold, Ketty La Rocca, Ulrike Rosenbach, Martha Rosler, Betye Saar, Miriam Schapiro, Carolee Schneemann, Cindy Sherman, Hannah Wilke
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; har4600; histoire et politique; premier cycle; périodes historiques; thématiques

Body art and performance: the body as language - Vergine, Lea; Vergine, Lea (Skira, 2007)
When The Body as Language ("Body-art" and Performance) appeared in 1974, it was immediately a huge publishing hit, reviewed by some of the most influential art historians and writers (Giulio C. Argan, Edoardo Sanguineti, Max Kozloff, Lucy Lippard, François Pluchart, Peter Gorsen, Evelyn Weiss and many others). A direct testimony of the birth and development of one of the most controversial art trends, Lea Vergine's book avails of a series of texts by the artists themselves, whom the author had asked to contribute with a statement about the illustrations of their work. Featuring a thorough documentation of original photographs and film photograms, videotapes, happenings, actions and performances, the book analyses the evolution of this phenomenon through the works of sixty artists, including Gina Pane, Gilbert & George, Urs Lüthi and Katharina Sieverding, Rebecca Horn, Trisha Brown, Günter Brus and many others who have worked with and on the body. In an absolutely unusual publishing event, nearly thirty years after the first edition, the text–by now a classic–is republished with all the original photographic material. The volume is enhanced and brought up-to-date by an afterword by Lea Vergine, who observes the changes of Body Art throughout the nineties: Orlan, Stelarc, Ron Athey, Franko B., Yasumasa Morimura, Jana Sterbak, Matthew Barney are "virtuosos of disorder and hungry for afflictions of any and every kind, mystics–like persons who display the subjection of their bodies to cruel and invasive devices, or who revel in virtual fantasies of such self-inflicted pains–destroy themselves in order newly to find themselves. . . . They finally pay a visit to the world of the saints and victims, exploring and prolonging its seductions.
Keywords: art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; performance; premier cycle; thématiques

Self image: technology, representation, and the contemporary subject - Jones, Amelia (Routledge, 2006)
"Self/Image explores the ways in which contemporary artists have deployed new technologies of representation, from analogue photography to more recent artistic practices including digital imaging, performance, robotics, film and video installations, to explore and articulate shifting modes of subjectivity. This book is one of the first full-length studies to investigate the complex intersubjective relations among these diverse artistic practices." "Including over 100 illustrations from mainstream film to independent film, video art, performance and the visual arts, this important and original book provides an excellent companion to more general studies of contemporary art history, and media and cultural studies in the post-1960 period."–Résumé de l'éditeur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; arts; arts visuels et médiatiques; corps; cours; discipline; film; har4600; histoire de l'art; performance; portrait; premier cycle; périodes historiques; représentation; thématiques; théorie de l'art

X-elles: le sexe par les femmes - Millet, Catherine..; Leydier, Richard 19.... (Art Press, 2004)
"Adresses Internet p. 112-113."Contient : Editorial : un raz de marée, par Catherine Millet et Richard Leydier, p. 5-7. Chapitre 1 : Elles débarquent! : L'acte pour l'art, par Louis-José Lestocart, p. 10-14 ; Bandes de femmes, par Bernard Joubert, p. 15-21 ; Éros féminin surréel, par Victoria Combalía, p. 22-27 ; Ellen von Unwerth. Naughty Girls!, interview par Richard Leydier, p. 28-31 ; Organes et orgasmes. Sur quelques chanteuses sexy, par Stéphane Pencréac'h, Stéphane Ruiz et Richard Leydier, p. 32-36; Dans le train fantôme de Catherine Breillat, témoignages recueillis par Brigitte Ollier, p. 37-40 ; Clarisse Hahn. La sexualité dans le tissu de la vie, interview par Catherine Millet et Louis-José Lestocart, p. 41-44 ; Portfolio #1 : Aude du Pasquier-Grall, Sonia Koumskoff-Raissi, Nicole Tran Ba Vang, Ornela Vorpsi, Friedl Kubelka, Anne Dion., p. 45-50. Chapitre 2 : Un autre porno : Angela, Loulou et les autres ... Quand les femmes prennent la caméra, par Stéphane Ruiz, p. 52-60 ; Monika Treut. Female Misbehavior, par Thibaut de Ruyter, p. 61-65 ; Maria Beatty. De la surface à la profondeur, par Catherine Corringer, p. 66-70 ; Shu Lea Cheang. Un genre en soi, Interview par Louis-José Lestocart, p. 71-74 ; Il y a une vie après le X : Brigitte, Tabatha, Ilona et Traci, par Laurent Goumarre, p. 75-80 ; Ovidie, plus librement, interview par Laurent Goumarre, p. 81-84 ; Portfolio #2 : Kiki Seror, Virginie Boursette, Béatrice Cussol, Bettina Rheims, Pascale Lafay, Diana Michener, p. 85-90. Chapitre 3 : Autoportraits : Lamia Ziadé. "Je suis une vraie petite femme d'intérieur", interview par Brigitte Ollier, p. 92-96 ; Chloë des Lysses. Une femme en danger, interview par Richard Leydier, p. 97-101 ; Madeleine Berkhemer. Élastique, érotique, par Alix Rozès, p. 102-105 ; Elke Krystufek. Le miroir qui met à nu, interview par Joerg Bader, p. 106-109 ; La pornographie, to remember, par Judith Brouste, p. 110-111 ; Les femmes sur le Web, par Chloë des Lysses, p. 112-113.
Keywords: 2000 à aujourd'hui; 2000-2009; arts; arts visuels et médiatiques; corps; cours; discipline; europe; france; har4600; histoire de l'art; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques

The art of history African American women artists engage the past - Collins, Lisa Gail (Rutgers University., 2002)
In this lively and engaging book, Lisa Gail Collins examines the work of contemporary African American women artists. Her study comes at a time when an unprecedented number of these artists-photographers, filmmakers, painters, installation and mixed-media artists-have garnered the attention and imagination of the art-viewing public. To better understand the significance of this particular historical moment in American visual arts, Collins focuses on four "problems" that recur when these artists confront their histories: the documentation of truth; the status of the black female body; the relationship between art and cultural contact and change; and the relationship between art and black girlhood. By examining the social and cultural histories which African American women artists engage, Collins illuminates a dialogue between past and present imagemakers. The Art of History is a major contribution to the study of American visual culture. It will be of use to both scholars and students in art history, African American studies, American studies, and women's studies.
Keywords: afro-féminisme; amériques; approches et analyses; arts visuels et médiatiques; corps; cours; discipline; fem1000; femmes* afro-américaines; féminisme afroaméricain; féminismes noirs; pratiques féministes; premier cycle; régions géographiques; thématiques; états-unis